Green process for green materials: viable low-temperature lipase-catalysed synthesis of renewable telechelics in supercritical CO2 - Curia, S.; Barclay, A.F.; Torron, S.; Johansson, M.; Howdle, S.M. (Royal Society of Chemistry, 2015)
We present a novel near ambient temperature approach to telechelic renewable polyesters by exploiting the unique properties of supercritical CO2 (scCO2). Bio-based commercially available monomers have been polymerised and functional telechelic materials with targeted molecular weight were prepared by end-capping the chains with molecules containing reactive moieties in a one-pot reaction. The use of scCO2 as a reaction medium facilitates the effective use of Candida Antarctica Lipase B (CaLB) as a catalyst at a temperature as low as 35 °C, hence avoiding side reactions, maintaining the end-capper functionality and preserving the enzyme activity. The functionalised polymer products have been characterised by 1H-NMR, MALDI-TOF, GPC and DSC in order to carefully assess their structural and thermal properties. We demonstrate that telechelic materials can be produced enzymatically at mild temperatures, in a solvent-free system and using renewably sourced monomers without pre-modification, by exploiting the unique properties of scCO2. The macromolecules we prepare are ideal green precursors that can be further reacted to prepare useful bio-derived films and coatings.